The Myth of Leda and the Swan Observed through the Prism of Rubén Darío ("Leda") and Delmira Agustini ("El cisne") (BEOIBERÍSTICA - Revista de Estudios Ibéricos, Latinoamericanos y Comparativos (ISSN: 2560-4163 Online), 2021)
The literary movement modernismo originated in Spanish America and gave birth to very important poets in Spanish American literature, bringing about novelties in poetry. Topics originating from classical history and mythology, Eastern civilizations and pre-Hispanic America were treated in an original way, which is one of its main novelties. That is also the topic of this paper, which considers the treatment of the Greek myth from the point of view of Nicaraguan poet Rubén Darío (1867–1916) and Uruguayan poet Delmira Agustini (Delmira Agustini, 1886–1914). The myth in question is about Leda and the swan, and the corpus includes the poems "Leda" ("Leda") written by Darío and "The Swan" ("El cisne") written by Agustini. The aim of this article is to point out the similarities and differences in the treatment of the aforementioned myth. Bearing in mind that Delmira Agustini is a part of the second generation of modernists, the so-called postmodernists, and Ruben Dario is the most important representative of modernismo at its peak, it is interesting, on one hand, to compare their interpretations and visions of this Hellenic myth, and on the other hand, to point out the extent to which mythological and symbolist elements are adopted, surpassed and, ultimately, matched in selected poems. Their interpretations of this myth differ greatly, and we came to this conclusion through a systematic analysis of the mentioned poems.Key words: Rubén Darío, Delmira Agustini, Greek mythology, Leda, swan.